Ganame Ousseni - Ninigui village (Yatenga province), Burkina Faso - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Ganame Ousseni is a farmer from Ninigui village in Burkina Faso. He describes the importance for farmers to heard cattle and how the climate change is forcing them to change their practice and to become decisive producers by both working in agriculture and raising cattle.